Microbiological, physicochemical and sensory parameters of dry fermented sausages manufactured with high hydrostatic pressure processed raw meat. (October 2015) - Omer, M.K.; Prieto, B.; Rendueles, E.; Alvarez-Ordoñez, A.; Lunde, K.; Alvseike, O.; Prieto, M.
Abstract: The aim of this trial was to describe physicochemical, microbiological and organoleptic characteristics of dry fermented sausages produced from high hydrostatic pressure (HHP) pre-processed trimmings. During ripening of the meat products pH, weight, water activity (aw ), and several microbiological parameters were measured at zero, eight, fifteen days and after 6 weeks. Sensory characteristics were estimated at day 15 and after six weeks by a test panel by using several sensory tests. Enterobacteriaceae were not detected in sausages from HHP-processed trimmings. Fermentation was little affected, but weight and aw of the HHP-processed sausages decreased faster during ripening. HHP-treated sausages were consistently less favoured than non HHP-treated sausages, but the strategy may be an alternative approach if the process is optimized. Highlights: Organoleptic properties of the end product change substantially when meat products are made from HHP-treated trimmings. HHP pre-processing of trimmings improves the hygienic quality of dry cured sausages. Before HHP can be applicable and valued by industry and consumers optimisation of process and recipes is needed.